THE RELIGIOUS ROLE OF LEADERSHIP MORALITY IN PREVENTING THE FRAUD OF GAMPONG FUNDS IN WEST ACEH DISTRICT - Arfriani Maifizar,; Lilis Marlina,; Sari Maulida Vonna,; Damrus,; Irwan Abdullah, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article analyzes the religious role in moderating the relationship between leadership morality in preventing the misappropriation of Gampong funds. This study aims to examine the effect of leadership morality on the prevention of village fund fraud and examine the religious role in moderating the relationship between leadership morality and the prevention of fraud (misappropriation) of Gampong funds (village fund) in West Aceh. This research uses quantitative research methodology. The sampling process in this study uses a purposive sampling method. Primary data was collected through a survey of 60 questionnaires given to the Gampong apparatus who occupy important positions in Gampong administration, namely Geuchik Gampong, Gampong secretary, head of the general subdivision of the village and treasurer of the village in Johan Pahlawan sub-district, Aceh Barat. The reason for choosing Johan Pahlawan sub-district as a research location is because the Johan Pahlawan sub-district is the center of the West Aceh Regency government with the largest population compared to other sub-district, so the budget allocation for the village fund is greater. The model used in this study is the MRA (Moderated Regression System) model. The partial test results of the regression model show that leadership morality is very influential in preventing the 112 misappropriation of village fund fraud with a parameter coefficient of 0, 017 and the significance is less than 0.05, level is 0.000. These results indicate that the higher the morality of leadership, the deviation from the Gampong funds decreases. While the residual test results in the MRA (Moderated Regression System) model show that religious values can moderate the relationship of leadership morality in preventing the misappropriation of village funds with absolute parameter efficiency values of -15, 281, and the significance level is 0,000. The coefficient value of the negative and significant parameters in the model shows that religion can be used as a moderating variable that can further strengthen the relationship of leadership morality in preventing the diversion of village funds